Legislative Discourse and Prohibited Discrimination Criteria: What Is Not Well Stated Cannot Be Well Qualified - Péru-Pirotte, Laurence (Translation Studies: Theory and Practice, 2023)
Discrimination is the difference in treatment based on criteria prohibited by law. It appears that the choice of criteria, as well as the way in which they are called by the legislator and then recognized by the courts is influenced by the discourse of the political powers in place. The article will focus in particular on the ambiguities relating to discrimination based on origin. The legislator is unable to sanction discrimination based on origin because it cannot qualify it without the power in place providing any key to do so. This results in difficulties in interpreting the criteria linked to origin expressed in the form of an unsatisfactory list. Solutions can be provided, in particular by clarifying the latter and by giving the generic term “racial and racist” discrimination.